India : Access of the Poor to Clean Household Fuels - World Bank (Washington, DC, 2014)
There is a strong case for phasing out price subsidies for liquefied petroleum gas (LPG) and kerosene. This study was motivated by the primary objective of facilitating access to clean fuels, given the significant health and social benefits of switching away from traditional biomass. Price subsidies have been found to be ineffective in expanding the uptake of LPG and kerosene as primary household fuels among the poor, and have proven fiscally unsustainable. Even given this social objective, phasing out the price subsidies for LPG and kerosene, and fostering a vibrant, open, and competitive market for these fuels would appear to be a better approach. The conclusions of this study lend strong support to the announcement by the Ministry of Finance in June 2003, that the LPG and kerosene subsidies will be phased down in three years, and eliminated by April 2006. There are significant opportunities to facilitate a shift away from traditional biomass, to clean fuels in urban and peri-urban areas, including among the poor; however, rural households are more difficult to deal with, and require a concerted multi-sectoral approach, but, raising public awareness about the health costs of traditional energy, would facilitate the uptake of clean fuels.